Dungeons (ideological) and dragons (cognitive): behavioral sciences and their role in the conceptualization of the climatic crisis - Bloise, Leo (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In recent years, numerous publications have appeared that try to generate a framework for the application of neurocognitive knowledge for the resolution of social problems. Under the nickname "behavioral sciences" this field of studies that is presented as deeply interdisciplinary is proposed social. We focus our gaze on certain epistemological and ideological aspects that underlie these initiatives, particularly regarding the conceptualization of the climatic crisis as a problem related to being solved through knowledge generated by cognitive sciences. We observe, exemplify and problematize a series of premises: the behavior of the individual as a terminal expression of an "internal" process in which the environment and by extension the "social" are subordinated in terms of their explanatory hierarchy, as suppliers of stimuli; The simplification of the problems to be solved in terms of biases and cognitive limitations, so that the objectives of the intervention are the behaviors and decisions of individual actors; The appeal to biology as an explanatory support for the validity of the psychological constructs used through the identification of neural correlates and adaptationist narratives on the development of innate cognitive functionalities. As observed, we maintain that the generation and application of knowledge in this type of initiatives is limited and in turn feeds a marked ideological line, according to which the main causes of the climate crisis are not found in the dynamics and contradictions of the socioeconomic system in force, but in those of individual cognitive systems. That is, conceivable interventions are about the consumption behaviors of individuals, but not on systemic dynamics of production and exploitation.